Education and Innovative Septic Tank: The Answer of Coastal Area Sanitation Problem - Chairunnisa Chairunnisa; Yuni Lisafitri (Penerbit Kemala Indonesia, 2018)
Development of innovative septic tank for Sebesi island has been conducted followed by education the danger of defecation improperly. The reactor was made by using the concept of anaerobic baffled reactor with polyethylene based materials. In the other hand, the education project was successfully conducted that can be seen from the public enthusiasm built the sanitation system followed by the change of community behavior